Financial impact of an analgosedation protocol for mechanically ventilated patients in a cardiovascular intensive care unit. (4th December 2019) - Devabhakthuni, Sandeep; Kapoor, Karan; Verceles, Avelino C; Netzer, Giora; Ludmir, Jonathan; Ramani, Gautam; Chaudhry, Amal; Bolgiano, Mary; Pollock, Jeremy S; Mccurdy, Michael T
Abstract: Purpose: The primary objective was to evaluate the impact of an analgosedation protocol in a cardiac intensive care unit (CICU) on daily doses and costs of analgesic, sedative, and antipsychotic medications. Methods: We conducted a single-center quasi-experimental study in 363 mechanically ventilated patients admitted to our CICU from March 1, 2011, to April 13, 2013. On March 1, 2012, an analgosedation protocol was implemented. Patients in the pre-implementation group were managed at the cardiologist's discretion, which consisted of a continuous sedative-hypnotic approach and opioids as needed. Patients in the implementation group were managed using this protocol. Results: The mean ± S.D. per-patient doses (mg/day) of propofol, lorazepam, and clonazepam decreased with the use of an analgosedation protocol (propofol 132, 265.7 ± 12, 951 versus 87, 980.5 ± 10, 564 [ p = 0.03]; lorazepam 10.5 ± 7.3 versus 3.3 ± 4.0 [ p < 0.001]; clonazepam 9.9 ± 8.3 versus 1.1 ± 0.5 [ p = 0.03]). The mean daily cost of propofol and lorazepam also significantly decreased (33.5% reduction in propofol cost [ p = 0.03]; 69.0% reduction in lorazepam cost [ p < 0.001]). The per-patient dose and cost of fentanyl (mcg/day) declined with analgosedation protocol use (fentanyl 2, 274.2 ± 2317.4 versus 1, 026.7 ± 981.4 [ p < 0.001]; 54.8% decrease in fentanyl cost [ p < 0.001]). Conclusion: The implementation of an analgosedation protocol significantly decreased both the use and cost of propofol, lorazepam, and fentanyl. Further investigation of the clinical impact and cost-effectiveness of a critical care consultation service with implementation of an analgosedation protocol is warranted in the CICU.